Oceanographic transport along frontal zones forms carbon, nitrogen, and oxygen isoscapes on the east coast of New Zealand: Implications for ecological studies. (1st March 2021) - Durante, L.M.; Smith, R.O.; Kolodzey, S.; McMullin, R.M.; Salmond, N.H.; Schlieman, C.D.; O'Connell-Milne, S.A.; Frew, R.D.; Van Hale, R.; Wing, S.R.
Abstract: Characterizing the spatial distribution of δ 18 O in seawater and δ 15 N and δ 13 C in marine particulate organic matter pools can be useful in identifying isotopic discriminators of major water masses and serve as a baseline for food web and other ecological studies. Nevertheless, we do not know how isoscapes of δ 18 O, δ 15 N and δ 13 C are distributed and interact with mesoscale (10–100 km) physical oceanographic features for large parts of the global ocean. Here samples and measurements were collected during research cruises in the austral summer of 2017/18 and 2018/19 along the east coast of the South Island of New Zealand. The physical structure of the water column, δ 18 O of seawater, and δ 15 N and δ 13 C of suspended particulate organic matter were analyzed. Interannual differences in inferred circulation, oceanographic features, and the interaction of Subtropical and Subantarctic water masses in the study area were described. The relationships between nutrient concentrations, physical oceanographic variables and δ 18 O, δ 15 N and δ 13 C isoscapes were investigated by running linear models with all combination of variables, then averaging the most parsimonious ones that best fit the data. Results demonstrate that different environments along the east coast are connected via northward transport of Subtropical Water near the surface and Subantarctic Mode Water at depth (220–500 m). The northward transport of modified STW was associated with nutrient inputs and deepening of the maximum fluorescence depth. The spatial distribution of isotopic values had minimal temporal variability and was primarily linked to patterns of nutrient input ( δ 15 N), coastal productivity ( δ 13 C) and water mass type ( δ 18 O). δ 15 N values demonstrated significant spatial variation, while δ 18 O displayed distinct values among depths. The present study was the first to resolve the distribution of δ 15 N and δ 13 C isotopes at a regional scale along the east coast of the South Island of New Zealand, δ 18 O in New Zealand waters, and to investigate the extent to which these distributions were influenced by patterns in physical oceanography. Average values of δ 18 O, δ 15 N and δ 13 C for different fishery management areas and depths are presented to support future ecological studies along Southeast New Zealand. Highlights: Subtropical and Subantarctic water masses connect habitats throughout the shelf. Habitat connectivity influences ocean productivity north of Akaroa. δ 15 N and δ 13 C isoscapes are influenced by nutrient availability and coastal advection patterns. δ 15 N and δ 13 C isoscapes vary spatially but showed small temporal variability.